Hemolysin activities as virulence factor of Enterococcus faecalis isolated from saliva and periapical abscess (gene detection by PCR) - Dewa Ayu N.P.A; Sari Dewiyani; Dessy Sulistya Ashari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Enterococcus faecalis is a normal flora of the oral cavity, commonly detected in saliva and persistence in endodontic infections. These bacteria have diverse survival and virulence factors. Hemolysin is one of the factor and still had unclear role as a virulence factor of the Enterococcus faecalis to survive in the root canal. Purpose: The purpose of this research was to analyze the presence and activity of hemolysin gene and its activity as a virulence factor isolated from saliva and root canals with periapical abscess. Yet by understanding one of the phenotypes characters which is hemolysin, it is expected a successful endodontic treatment can be provided with the persistent of Enterococcus faecalis bacteria. Methods: Method of the research starting with the identification of Enterococcus faecalis bacteria in isolated saliva and periapical abscess was done in the first part of the study. Then the phenotypes character of Enterococcus faecalis such as gene detection and expression of hemolysin in blood agar cultures of the 60 colonies samples were performed in the later part. Results: Not all of the colonies cultured were identified as Enterococcus faecalis. All positive detection on hemolysin gene showed hemolysin expresion in both isolated samples. However, there were samples with hemolysin expression eventough no hemolysin gene detected. Hemolysin expression detection in saliva was higher due to different activation phase of hemolysin in saliva. The study with just one primer could lead to the possibility of undetected hemolysin gene, eventough there were samples that did not have hemolysin gene. The proportion of hemolysin expression in root canals were less than saliva, this could be influenced by environmental factors. However, Hemolysin was considered as important virulence factor, particularly for disease therapy. Conclusion: The conclusion of this research was hemolysin gene discovered in clinical isolated saliva and root canals samples as virulence factor of the Enterococcus faecalis, and hemolysin expression occured from both sources.Latar belakang: Bakteri Enterococcus faecalis adalah flora normal rongga mulut dan merupakan mikroorganisme yang umum dideteksi dalam saliva dan infeksi endodontik persistensi. Bakteri ini memiliki berbagai faktor survival dan virulensi. Hemolysin adalah salah satunya tetapi masih merupakan faktor virulensi yang belum terlalu jelas mekanismenya. Tujuan: Tujuan riset ini adalah untuk menganalisis keberadaan gen hemolysin dan aktifitas hemolysin Enterococcus faecalis sebagai faktor virulen yang diisolasi dari saliva dan saluran akar gigi dengan abses periapikal. Mengetahui salah satu karakter fenotip Enterococcus faecalis yaitu hemolysin diharapkan berguna untuk kesuksesan perawatan endodontik akibat pesistensinya bakteri tersebut. Metode: Penelitian diawali pada bagian pertama penelitian adalah identifikasi bakteri Enterococcus faecalis isolat saliva dan abses periapikal. Bagian kedua melihat karakter fenotip Enterococcus faecalis berupa deteksi gen hemolysin serta ekspresi hemolysin di kultur agar darah dari 60 sampel koloni. Hasil: Tidak semua kuman yang tumbuh dikultur teridentifikasi sebagai Enterococcus faecalis. Pada deteksi gen hemolysin positif menunjukkan seluruhannya terekspresi hemolysin di kedua sumber isolat klinik. Namun, terdapat sampel yang menunjukkan terekspresi hemolysin meskipun gen hemolysin tidak ada dan itu lebih banyak di saliva, walaupun tidak bermakna. Hal ini dapat disebabkan perbedaan tahap aktivasi hemolysin di saliva. Pengujian hanya dengan satu primer dapat menyebabkan kemungkinan ada gen hemolysin tetapi tidak terdeteksi. Walaupun memang ada sampel yang tidak memiliki gen hemolysin. Proporsi keberadaan ekspresi hemolysin pada saluran akar lebih sedikit dari saliva karena ekspresi hemolysin dipengaruhi faktor lingkungan. Namun demikian, Hemolysin adalah faktor viruensi yang penting khususnya untuk terapi penyakit. Kesimpulan: Kesimpulan penelitian ini adalah ditemukan gen hemolysin pada sampel isolat klinik saliva dan saluran akar sebagai faktor virulen bakteri Enterococcus faecalis serta terjadi ekspresi hemolysin dari kedua sumber tersebut.